Resilience Assessment of Road Networks in the Extremely Severe Disaster Areas of the Wenchuan Earthquake - Wei, Meng; Fang, Song Jing; Chen, Sang; Lin, Ran yi; Huang, Yong; Yang, Li (Frontiers in Earth Science, 2022)
On May 12, 2008, a 7.9 earthquake hit Wenchuan County, Aba Tibetan and Qiang Autonomous Prefecture in Sichuan Province, causing substantial losses of human lives and property. This paper takes ten counties and cities of the road network in the extremely severe disaster areas of the Wenchuan earthquake as research objects and extracts typical road network characteristics for 10 time points during the pre-earthquake, damage and repair process, then builds three resilience assessment indices, namely, the overall integrity, overall connectivity and effective connectivity with the complex network and resilience framework, to investigate the road network resilience. A resilience curve of the road system based on real data from the extremely severe disaster areas of the Wenchuan earthquake is obtained for the first time, revealing the total variation characteristics and key sections of the road system in terms of toughness and proposing hypothetical strategies for resilience optimization.